Against school: an epistemological critique. Issue 6 (2nd November 2022) - Ball, Stephen; Collet-Sabé, Jordi
ABSTRACT: The paper argues that the modern school is an 'intolerable' institution. 1 Contrary to the sensibilities of educational research that look for more and/or better schooling as a way of making education more equal and more inclusive, our position is against the modern European school as an institution of normalisation within which equality and inclusion are impossible. Foucault's strategy of reversal is used as a means of subversion to argue for an end to schooling. Concretely the paper highlights the epistemic fundamentals of the modern school and in particular the dynamics of normalisation related to the universal and the production of inequalities and isolated individuals. The paper asserts the need to be 'against' rather than 'for' the school and the abandonment of the 'redemptive perspective'. Over and against this, we propose the need to think education differently and apart from the school in order to open up other educations, and specifically education as an ethical activity, an exploration of limits, and a politics of the self.